The Effectiveness of Neuromuscular Taping (NMT) And Foot Exercise in Improving Microsirculations in Diabetes Mellitus Patients - Susanti, Indah; Arofiati, Fitri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background: Diabetes mellitus is a chronic disease characterized by abnormal glucose due to disturbances in the pancreas. Neuromuscular Taping (NMT) is a non-pharmacological intervention to prevent decreased peripheral blood circulation of the lower extremities. Prevention of complications in patients with diabetes mellitus can also be done by improving the vascularization of the feet by doing foot exercises. Objective: This study aims to compare the effectiveness of Neuromuscular Taping (NMT) and foot exercise on the improvement of the Ankle Brachial Index (ABI) value. Methods: Quantitative research design with quasi-experimental methods pre-test and post-test with control group design. The population in this study was 356 patients, a sample of 66 respondents. The sampling technique used was purposive sampling with inclusion and exclusion criteria. Results: there is an effect on changes in the value of the Ankle Brachial Index (ABI) before and after the intervention of Neuromuscular Taping (NMT) and diabetic foot exercise. There was a significant difference between the intervention group and the control group on changes in the value of the Ankle Brachial Index (ABI). Conclusions and suggestions: there is an effect on changes in the value of the Ankle Brachial Index (ABI) before and after being given Neuromuscular Taping (NMT) and diabetic foot exercises. There was a significant difference between the intervention group and the control group on changes in the value of the Ankle Brachial Index (ABI). Suggestion: Neuromuscular Taping (NMT) and diabetic foot exercise can be a reference in providing education and nursing interventions to be applied in hospitals as a preventive measure to prevent microvascular complications, especially in patients with diabetes mellitus. Abstrak: Latar Belakang: Diabetes mellitus merupakan suatu penyakit kronis yang ditandai dengan glukosa yang abnormal karena terjadi gangguan pada pankreas. Neuromuscular Taping (NMT) adalah salah satu intervensi non farmakologi untuk mencegah pernurunan sirkulasi darah perifer ekstremitas bawah. Pencegahan komplikasi pada pasien diabetes mellitus dapat juga dilakukan dengan memperbaiki vaskularisasi kaki dengan melakukan senam kaki. Tujuan: Penelitian ini bertujuan untuk membandingkan efektivitas Neuromuscular Taping (NMT) dan senam kaki terhadap perbaikan nilai Ankle Bracial Indeks (ABI). Metode: Desain penelitian kuantitatif metode quasi eksperimental pre-test and post-test with control group design. Populasi dalam penelitian ini sebanyak 356 pasien, sampel 66 responden. Teknik pengambilan sampel dalam menggunakan purposive sampling dengan kriteria inklusi dan eklusi. Hasil: ada pengaruh terhadap perubahan nilai Ankle Brachial Index (ABI) sebelum dan sesudah diberikan intervensi Neuromuscular Taping (NMT) dan senam kaki diabetes. Terdapat perbedaan yang signifikan antara kelompok intervensi dan kelompok kontrol terhadap perubahan nilai Ankle Brachial Index (ABI). Kesimpulan dan saran: ada pengaruh terhadap perubahan nilai Ankle Brachial Index (ABI) sebelum dan sesudah diberikan intervensi Neuromuscular Taping (NMT) dan senam kaki diabetes. Terdapat perbedaan yang signifikan antara kelompok intervensi dan kelompok kontrol terhadap perubahan nilai Ankle Brachial Index (ABI). Saran: Neuromuscular Taping (NMT) dan senam kaki diabetes dapat menjadi referensi dalam pemberian edukasi maupun intervensi keperawatan untuk diaplikasikan di rumah sakit sebagai tindakan preventif pencegahan komplikasi mikrovaskular khususnya pada pasien diabetes mellitus.